THE OPERATIONAL MANAGEMENT OF NAVY HUMAN RESOURCES FOR IMPROVING THE QUALITY OF NAVY PERSONNEL - Elisabeth Tanti Pudiastuti (JOURNAL ASRO, 2020)
The importance of the role of Operational Management and Human Resources are closely related toperformance quality of the Indonesian Navy personnel. There is a must-have for every personnel toimprove the optimal performance of competence development. The problem discussed in thisresearch is how the operational management to improve the performance of Indonesian NavyPersonnel. The purpose of this research is to know the relation of performance quality ocompetence toNavy performance support instrument and to analyze the influence of Human Resources on Navyperformance. The method used is descriptive analysis of the influence of teh Operational ManagementHuman Resources on performance. Based on the results of the study, a person with adequateexperience and technical qualifications, not necessarily have good performance, if the concerned isunable to show the behavior that supports the implementation of the task.Keyword: Operational Management, Navy Human Resources, Performance Quality